PENGARUH HIDROGEN SIANAMIDA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TEH (Camellia sinensis (L.) O. Kuntze) SETELAH PEMANGKASAN - Ahmad Junaedi; Slamet Susanto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1996)
The experiment was aimed to study the effect of hydrogen cynamide on tea growth and production after pruning. The experiment was conducted at Goalpara Tea Plantation (1100 m above sea levels) from September 1994 to March 1995. Clone TR12025 planted in 1976 with 29 months pruning cycle was pruned a week before application of hydrogen cynamide. Randomized Complete Block Design was used in this experiment with four treatments and four replications. Treatments consist of hydrogen cynamide 0.00 % (control), 0.50 %, 1.25 % and 2.50 %. An experiment unit consists of 20 tea plants. The results showed that treatments of hydrogen cynamide was not significantly increase the number of shoots and weight of